Texture and residual stress within rotary swaged Cu/Al clad composites - Kunčická, Lenka; Kocich, Radim; Strunz, Pavel; Macháčková, Adéla (Materials letters, 2018)
Innovative Cu/Al clad composites with unique sequencing were rotary swaged at 20 °C and 250 °C with various swaging degrees. The analyses carried out by electron microscopies and neutron diffraction focused on deformation behaviour of the component metals, grains orientations, occurrence of residual stress and possible development of intermetallic phases on the interfaces. The results showed the swaging temperature and total imposed strain to have significant influences on all the investigated parameters. The Al wires cross-sections within the composites were affected by the increasing total imposed strain more at 250 °C, these composites also exhibited formation of intermetallics at higher swaging degrees. However, according to the neutron diffraction results, all the swaged composites experienced structure restoration resulting in residual stress relaxation despite the fact that they exhibited texture formation. Rotary swaging was proven to be applicable for production of Cu/Al clad composite wires in the industrial scale.